Delineation of Nickel Laterite Deposits in "DCV" Block Southeast Sulawesi Based on Data Analysis of Ground Penetrating Radar (GPR) Method - Yatini, Y; Getsimany, Chrismast (Jambura Geoscience Review, 2024)
The need for nickel is very intensive in the development of upstream to downstream industries so that domestic consumption of nickel ore will increase in the coming years, therefore domestic downstream is increasingly being improved. Overcoming the problem of the high demand for nickel in Indonesia can be done by conducting exploration and exploitation to support the downstream of nickel. Exploration of nickel laterite can be accomplished with geophysical methods that aim to obtain subsurface data from nickel laterite deposits. The Ground Penetrating Radar (GPR) geophysical method is one of the non-destructive methods that can be applied to determine the subsurface conditions of nickel laterite deposits based on physical properties in the form of dielectric constants and reflection patterns and amplitude contrasts produced on radargrams. The nickel laterite deposits can be separated into 4 layers based on Ground Penetrating Radar (GPR) data analysis: bedrock, saprolite, limonite, and topsoil. Based on GPR measurements, the average dielectric constant value of topsoil is 6.8 mS/m, the limonite layer is 10.87 mS/m, the saprolite layer is 12.37 mS/m, and bedrock is 7.87 mS/m. It can be seen that the saprolite layer has a high conductivity so that the dielectric constant value is also high, this is influenced by the very high nickel content in this layer. The depth of bedrock in the research area varies from 20 - 40 meters, the thickness of topsoil is dominated in the value range of 3.6 - 5 meters, while the thickness of the laterite layer which is the main target of nickel laterite mining includes saprolite and limonite layers which have varying values of 15 - 40 meters where the distribution of the thickness of this layer is in the eastern and central parts of the research area.